Routine assessment of performance status during palliative chemotherapy when approaching end-of-life. (April 2016) - Näppä, Ulla; Lindqvist, Olav; Rasmussen, Birgit H.; Axelsson, Bertil
Abstract: Purpose: Palliative chemotherapy treatment (PCT) offered late in the cancer disease trajectory may be problematic. It is not easy to accurately calculate whether the potential benefits will outweigh the side-effects. This study investigates whether routine use of the Performance Status in Palliative Chemotherapy questionnaire (PSPC) affects the proportions of patients receiving PCT during the last month of life, care utilization, and documentation routines. A secondary aim was to gather registered nurses' experiences of the PSPC in routine use. Methods: Eighty incurable patients with cancer who had used the PSPC before PCT were compared to 160 matched controls, using non-parametric tests. Nurses' reflections on the PSPC were collected and reviewed. Results: No significant differences were found between users and non-users of the PSPC in terms of proportions receiving PCT during the last month of life. Higher proportions of patients older than 74 years received PCT than in previous studies (40% versus 17%). Nurses considered the questionnaires to be a valuable complement to verbal information when trying to acquire an accurate picture of patients' performance status. Conclusion: At this point in the development of the PSPC we did not find any significant decreases in the proportion of patients receiving PCT during the last month in life. However, as the nurses valued the PSPC, it can be used as a complementary tool in assessment of performance status until further research is conducted. Highlights: The PSPC provided complementary information about performance status in PCT. Place of death or hospital admissions after last PCT were not influenced by the PSPC. More patients older than 74 are receiving PCT than previously described from the area.